The Effect of Servant Leadership on Work Engagement: The Mediating Role of Person-Organization Fit - Gökhan Kenek (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi, 2024)
This study aimed to explore the relationship between servant leadership and work engagement and investigate the mediating role of person-organization fit in this relationship. The research was conducted in July 2023 on blue-collar employees in the glass industry in the Marmara Region. A total of 266 employees participated in the survey. Confirmatory factor analyses (CFA) were conducted using the MPLUS7 package program, and hypotheses were tested using the SPSS26 program. The results of the analyses indicated that servant leadership positively influences person-organization fit and work engagement. Additionally, it was found that person-organization fit increases work engagement. Furthermore, it was revealed that person-organization fit partially mediates the effect of servant leadership on work engagement.